Examination of Changes of Oropharynx Flora Related to Hospitalization - Z Aminzadeh; M Molla Abedin; MM Soltan Dallal; L Gatchkar (Tehran University of Medical Sciences, 2003)
According to changes in the surface of respiratory epithelial cells and host immunity as well as virulence of hospital acquired pathogens, oropharyngeal colonization enhance in hospital admitted patients. Patient admission in hospital, due to changes of oropharyngeal flora and colonization of virulent germs such as Staphylococcus aureus and gram negative bacilli can be a serious problem for developing respiratory infections and nosocomial septicemia. This investigation was carried out on effects of residency of patients in the hospital by oropharyngeal flora. This was a Quasi-clinical trial and assembled data is based on observation and interview. Oropharyngeal germ samples of 30 admitted patients in dermatology ward of Loghman hospital were cultivated at the first and fifth day of admission. All the colonies were distinguished by microbiologists. Thirty patients at the range of 44± 20 years of age were studied. There have been history of corticosteroid usage in 16 persons (53%) and usage of a cytotoxic drug in 8 persons (27%).There has been α- hemolytic Streptococci in 100% of patients, Neisseria in 87% , coagulase positive Staphylococci in 3%, yeast in 3% and gram negative bacilli in 13% of the patients at the beginning of admission. At the fifth day of admission, α - hemolytic Streptococci & Neisseria had the same values as they were at the first, but colonization of coagulase positive Staphylococci increased by 30% , the increase of the yeast was 23%. According to this study changes of oropharyngeal flora in a 5 days admission were statistically significant for coagulase positive Staphylococci and yeast but these changes are not significant for other investigated germs.